Plant mitochondria - Kempken, Frank; SpringerLink (Online service). (New York Springer, 2011)
Mitochondria are the product of a long evolutionary history. It is now a well established fact that mitochondria did evolve from free living bacteria being the common ancestor of both, eukaryotic mitochondria and ?-proteobacteria. Advances in genome sequencing, the establishment of in organello and in vitro assays to name only a few, contributed significantly to advances in plant mitochondrial research. Second generation sequencing and the ability to directly sequence and analyse the whole plant transcriptome certainly will help to develop the research on plant mitochondria to another level in the future. In this book the current knowledge about plant mitochondria is presented in a series of detailed chapters, which have been organized in five main sections: (i) dynamics, genes and genomes; (ii) transcription and RNA processing; (iii) translation and import; (iv) biochemistry, regulation and function; and (v) mitochondrial dysfunction and repair. These sections consist of two to five chapters, each written by well-known specialists in the field. This book thus provides a comprehensive inside in the field of plant mitochondria for the specialist. The addition of a glossary and text boxes to each chapter provides easy access for readers from other subjects and hopefully will attract young scientist to the fascinating and exiting field of plant mitochondria. Frank Kempken graduated from the Ruhr-University Bochum, Germany. He is professor for genetics and molecular biology in botany at the Christian-Albrechts-University at Kiel, Germany.
Preface: Introduction to plant mitochondria.-Dynamics, Genes & Genomes -- Evolutionary origin and endosymbiotic aspects of mitochondria -- Dynamics of mitochondrial shape, size etc -- Plant mitochondrial genomes & recombination -- Transcription & RNA processing -- Transcription in plant mitochondria -- RNA processing and RNA stability -- RNA splicing -- RNA editing -- RNA binding proteins required for chloroplast RNA processing -- Translation & Import -- Translation and mitochondrial proteom in plants -- Import of RNAs into plant mitochondria -- Import of proteins into plant mitochondria -- Mitochondrial import in fungi and animals -- Biochemistry, Regulation & Function -- Biogenesis and supramolecular organization of mitochondrial membrane complexes in plants -- Electron Transport & Stress -- Interaction of mitochondria and plastids (and other cellular compartments?) -- Mitochondrial retrograde regulation -- Programmed cell death -- Mitochondrial Dysfunction & Repair -- Cytoplasmic male sterility & fertility restoration by nuclear genes Human mitochondrial mutations and repair.
Electronic reproduction.
Keywords: Plant mitochondria; Electronic books